A Study of the Construction of Tony Loneman’s Self in There There from the Perspective of Mirror Image - xu, mengyao (Pacific International Journal, 2025)
There There, the debut novel by Tommy Orange, breaks away from the traditional “homing in plots” often associated with Native American narratives. This work vividly portrays the struggles of urban Native Americans as they navigate cultural heritage and societal prejudice to achieve self-identity and identity reconstruction. From the perspective of Lacan’s mirror theory, this paper analyzes the process of self-construction of Tony Loneman in Tommy Orange’s novel There There. Tony, grappling with fetal alcohol syndrome, undergoes an identity crisis, moving through the chaotic pre-mirror stage, the self-awakening mirror stage, and the identity-reconstructing post-mirror stage. In the pre-mirror stage, Tony is unable to form a coherent self-image through external reflections, existing in a state of “fragmented body”. During the mirror stage, he begins to break free from the gaze of the "Other" through Native American traditions, his grandmother’s guidance, and the music of Daniel Dumile, actively constructing his self-identity. In the post-mirror stage, Tony’s heroic actions during the shooting at the Powwow mark the culmination of his self-identity, transcending the dependency of the mirror stage and achieving a reconstruction of subjectivity. Tony’s struggle not only reveals the identity crisis and self-redemption of individuals within multicultural contexts but also offers profound insights into the identity struggles of Native Americans in the face of modernization.